THE DYNAMICS OF INDONESIA LUMAJANG FOOTBALL CLUB IN 1947-2018 - Finsa Zainal; Kayan Swatika; Sugiyanto Sugiyanto (JURNAL HISTORICA, 2020)
Abstract Football is the most beloved sport in Indonesia, not only by adults, children, even women play it. Football clubs are also an expression of identity for regional and. Almost every region has a football club, no exception in Lumajang district. The Lumajang Indonesian Football Association (PSIL) has a long history of National Association. But the history of the establishment until the competition in Indonesia is still a junction. Prolonged internal problems have an impact on achievement in competitions. The highest achievement by PSIL Lumajang was able to pass the Division I in 2001 and then Fakum participated in the competition. In 2012 PSIL Lumajang was able to penetrate the division I again until the competition system changed in the year 2017 to Liga 3. During the 1947 to 2018 period, PSIL Lumajang experienced a rise in progress and achievement. Keywords: Sepak bola, PSIL, Lumajang.